"Movements Come and Go and Are Soon Forgotten": The Black Campus Movement at Fayetteville State, 1966-1972. (20th September 2022) - Turner, Francena
Abstract : Broad surveys of college student activism are impossible without the study of individual campuses. Studies of activism on historically Black college and university (HBCU) campuses in the United States tend to focus on larger more well-known campuses or those in large urban areas. Studies of student activism within North Carolina repeatedly highlight only three of the eleven extant institutions. This study contributes to the historiography of Black campus activism by using nine oral history interviews conducted with university alumni paired with extensive archival research to excavate the ways Fayetteville State University students contributed to the Black Campus Movement. This essay is a narrative of student protests between 1966 and 1972. Ultimately, such protests were grounded in major breakdowns in meaningful communication between faculty, administrators, alumni, and students and in HBCU students' shared desire to have a say in decisions that affected their lives. Fayetteville State's student body fully invoked James Baldwin's notion of critiquing America in that they loved their institution more than any other institution in the world, and, exactly for that reason, they insisted on the right to criticize Fayetteville State and demanded that she rise to the occasion for which she was formed.